Interdisciplinary Diagnosis, Therapy and Follow-up of Patients with Endometrial Cancer. Guideline (S3-Level, AWMF Registry Number 032/034-OL, April 2018) – Part 2 with Recommendations on the Therapy and Follow-up of Endometrial Cancer, Palliative Care, Psycho-oncological/Psychosocial Care/Rehabilitation/Patient Information and Healthcare Facilities - Emons, Günter; Steiner, Eric; Vordermark, Dirk; Uleer, Christoph; Bock, Nina; Paradies, Kerstin; Ortmann, Olaf; Aretz, Stefan; Mallmann, Peter; Kurzeder, Christian; Hagen, Volker; van Oorschot, Birgitt; Höcht, Stefan; Feyer, Petra; Egerer, Gerlinde; Friedrich, Michael; Cremer, Wolfgang; Prott, Franz-Josef; Horn, Lars-Christian; Prömpeler, Heinrich; Langrehr, Jan; Leinung, Steffen; Beckmann, Matthias W.; Kimmig, Rainer; Letsch, Anne; Reinhardt, Michael; Alt-Epping, Bernd; Kiesel, Ludwig; Menke, Jan; Gebhardt, Marion; Steinke-Lange, Verena; Rahner, Nils; Lichtenegger, Werner; Zeimet, Alain; Hanf, Volker; Weis, Joachim; Mueller, Michael; Henscher, Ulla; Schmutzler, Rita K.; Meindl, Alfons; Hilpert, Felix; Panke, Joan Elisabeth; Strnad, Vratislav; Niehues, Christiane; Dauelsberg, Timm; Niehoff, Peter; Mayr, Doris; Grab, Dieter; Kreißl, Michael; Witteler, Ralf; Schorsch, Annemarie; Mustea, Alexander; Petru, Edgar; Hübner, Jutta; Rose, Anne Derke; Wight, Edward; Tholen, Reina; Bauerschmitz, Gerd J.; Fleisch, Markus; Juhasz-Boess, Ingolf; Lax, Sigurd; Runnebaum, Ingo; Tempfer, Clemens; Nothacker, Monika J.; Blödt, Susanne; Follmann, Markus; Langer, Thomas; Raatz, Heike; Wesselmann, Simone; Erdogan, Saskia (Geburtshilfe und Frauenheilkunde, 2018)
Summary The first German interdisciplinary S3-guideline on the diagnosis, therapy and follow-up of patients with endometrial cancer was published in April 2018. Funded by German Cancer Aid as part of an Oncology Guidelines Program, the lead coordinators of the guideline were the German Society of Gynecology and Obstetrics (DGGG) and the Gynecological Oncology Working Group (AGO) of the German Cancer Society (DKG).Purpose Using evidence-based, risk-adapted therapy to treat low-risk women with endometrial cancer avoids unnecessarily radical surgery and non-useful adjuvant radiotherapy and/or chemotherapy. This can significantly reduce therapy-induced morbidity and improve the patientʼs quality of life as well as avoiding unnecessary costs. For women with endometrial cancer and a high risk of recurrence, the guideline defines the optimal extent of surgical radicality together with the appropriate chemotherapy and/or adjuvant radiotherapy if required. An evidence-based optimal use of different therapeutic modalities should improve the survival rates and quality of life of these patients. This S3-guideline on endometrial cancer is intended as a basis for certified gynecological cancer centers. The aim is that the quality indicators established in this guideline will be incorporated in the certification processes of these centers.Methods The guideline was compiled in accordance with the requirements for S3-level guidelines. This includes, in the first instance, the adaptation of source guidelines selected using the DELBI instrument for appraising guidelines. Other consulted sources included reviews of evidence, which were compiled from literature selected during systematic searches of literature databases using the PICO scheme. In addition, an external biostatistics institute was commissioned to carry out a systematic search and assessment of the literature for one part of the guideline. Identified materials were used by the interdisciplinary working groups to develop suggestions for Recommendations and Statements, which were then subsequently modified during structured consensus conferences and/or additionally amended online using the DELPHI method, with consent between members achieved online. The guideline report is freely available online.Recommendations Part 2 of this short version of the guideline presents recommendations for the therapy of endometrial cancer including precancers and early endometrial cancer as well as recommendations on palliative medicine, psycho-oncology, rehabilitation, patient information and healthcare facilities to treat endometrial cancer. The management of precancers of early endometrial precancerous conditions including fertility-preserving strategies is presented. The concept used for surgical primary therapy of endometrial cancer is described. Radiotherapy and adjuvant medical therapy to treat endometrial cancer and uterine carcinosarcomas are described. Recommendations are given for the follow-up care of endometrial cancer, recurrence and metastasis. Palliative medicine, psycho-oncology including psychosocial care, and patient information and rehabilitation are presented. Finally, the care algorithm and quality assurance steps for the diagnosis, therapy and follow-up of patients with endometrial cancer are outlined.Zusammenfassung Im April 2018 erschien die erste deutsche interdisziplinäre S3-Leitlinie für die Diagnostik, Therapie und Nachsorge der Patientinnen mit Endometriumkarzinom. Von der Deutschen Krebshilfe im Rahmen des Leitlinienprogramms Onkologie gefördert, wurde sie von der Deutschen Gesellschaft für Gynäkologie und Geburtshilfe (DGGG) und der Arbeitsgemeinschaft Onkologische Gynäkologie (AGO) der Deutschen Krebsgesellschaft (DKG) federführend koordiniert.Ziele Durch eine evidenzbasierte risikoadaptierte Therapie können bei den Frauen mit Endometriumkarzinom mit geringem Risiko eine unnötige Radikalität bei der Operation und nicht sinnvolle adjuvante Strahlen- und/oder Chemotherapie vermieden werden. Dies reduziert zum einen deutlich die therapieinduzierte Morbidität und erhöht die Lebensqualität der Patientinnen. Auf der anderen Seite werden unnötige Kosten vermieden. Für die Frauen mit einem Endometriumkarzinom mit hohem Rezidivrisiko definiert die Leitlinie die optimale operative Radikalität sowie die ggf. erforderliche Chemotherapie und/oder adjuvante Strahlentherapie. Durch den evidenzbasierten optimalen Einsatz der verschiedenen Therapiemodalitäten sollten Überleben und Lebensqualität dieser Patientinnen verbessert werden. Die S3-Leitlinie zum Endometriumkarzinom soll eine Grundlage für die Arbeit der zertifizierten gynäkologischen Krebszentren sein. Die auf dieser Leitlinie basierenden Qualitätsindikatoren sollen in den Zertifizierungsprozess dieser Zentren einfließen.Methoden Die Leitlinie wurde gemäß den Anforderungen eines S3-Niveaus erarbeitet. Dies umfasst zum einen die Adaptation der mittels des DELBI-Instruments selektierten Quellleitlinien. Zum anderen Evidenzübersichten, die anhand der in systematische Recherchen nach dem PICO-Schema in ausgewählten Literaturdatenbanken selektierten Literatur erstellt wurden. Ergänzend wurde ein externes Biostatistik-Institut mit der systematischen Literaturrecherche und -Bewertung eines Teilbereichs beauftragt. Diese Ergebnisse dienten den interdisziplinären Arbeitsgruppen als Basis für die Erarbeitung von Vorschlägen für Empfehlungen und Statements, welche in strukturierten Konsensuskonferenzen und/oder ergänzend im DELPHI-Verfahren auch online modifiziert und konsentiert wurden. Der Leitlinienreport ist online frei verfügbar.Empfehlungen Der Teil 2 dieser Kurzversion der Leitlinie zeigt Empfehlungen zur Therapie des Endometriumkarzinoms, inklusive der Präkanzerosen und des frühen Endometriumkarzinoms, zur Palliativmedizin, Psychoonkologie, Rehabilitation und Patientinnenaufklärung und zu den Versorgungsstrukturen des Endometriumkarzinoms: Das Management von Präkanzerosen und frühen Endometriumkarzinomen, inklusive fertilitätserhaltender Strategien, wird dargestellt. Das Konzept der operativen Primärtherapie des Endometriumkarzinoms wird behandelt. Weiterhin werden die Strahlentherapie und die adjuvante medikamentöse Therapie des Endometriumkarzinoms und der uterinen Karzinosarkome abgebildet. Es werden Empfehlungen zur Nachsorge des Endometriumkarzinoms, zum Rezidiv und zur metastasierten Situation gegeben. Die Bereiche Palliativmedizin, Psychoonkologie, einschließlich psychosozialer Betreuung und Patientinnenaufklärung, und Rehabilitation werden dargelegt. Abschließend werden der Versorgungsalgorithmus und die Qualitätssicherungsschritte für die Diagnostik, die Therapie und die Nachsorge der Patientinnen mit Endometriumkarzinom vorgestellt.
Keywords: endometrial cancer; guideline; precancers; therapy; follow up